Commodification of the Urban Community Image: An Instagram Case Study of Motivational Quotes and Skyscraper Photo - Azkiya Nisa; Maria Regina Widhiasti; Euis Puspita Dewi (International Journal of Management, Entrepreneurship, Social Science and Humanities, 2022)
Rapid technology advancements, particularly social media Instagram, have brought people’s daily lives and urban environments into the domain of visual culture. Instagram’s young users are presently sharing motivational quotes adopted in activities and work with the use of a skyscraper as a background. The trend of encouraging quotes and skyscaraper photographs exemplifies the community’s orientation, which refers to a lifestyle or a typical phenomenon of Indonesian urban culture. This article intends to investigate the image of society by using Instagram to post encouraging phrases and patterns of space production-consumption using images of buildings taken by young people. The method of social semiotics was employed in this article with qualitative approach. Guy Debord’s Spectacle of Society (1967) theory and the postmodernist perspective are also discussed. Instagram creates a dichotomy with its picture of modern society and stunning metropolitan areas. Consumption and self-commodification are discussed in the context of capitalism through artistically potrayed public life performances on Instagram. As a result, a new concept of conflicting urban spaces emerges. On the one hand, an idealized portrayal of communal life and urban space exists, while the other side of a city with dense populations is ignored. This study is limited the social media platform Instagram and the Jakarta metropolitan area in Indonesia. There has never been a conversation about the convergence of urban settings with social media as a spectacle before.